Computational fluid dynamic simulation of the non-newtonian flow in a 3D printing process - Lee, Kai Theng (Nanyang Technological University, 2020)
The introduction of 3D bioprinting first begin in the late 20th century and it has become a rapidly emerging technology, widely recognised around the world for its capability to fabricate living organ for transplantation, prosthetics and 3D tissue models for drug testing. In 3D bioprinting, it incorporates the use of bio-ink made up of several living cells combined with its compatible base into different printing technique to fabricate a biomedical structure that mimic the characteristic of natural tissue. However, the difficulties faced during the process of bioprinting lies with the ability to retain the biological and physical properties of these living cells before, during and after printing. In this project, a 2D Computational Fluid Dynamic simulation was conducted using an overset meshing technique to analyse the stresses experienced by an alginate gel particle immersed in a fluid stream of different viscosity. Additionally, based on the relevant stresses obtain, a demonstration of an uncoupled fluid-structure interaction over a deformable body will be carried out using ABAQUS. The investigation of particle deformation in microfluidic constrictions is relevant to also serve as a model to understand the biological phenomena, for instance, the behaviour of the red blood cells when it is moving through a narrow blood vessel.